Experimental investigations on a topology-optimised thermal energy storage device filled with novel phase change materials - Chua, Cher Shean (Nanyang Technological University, 2020)
Thermal energy is the most abundant form of energy in the world. A significant amount of work has been done to enhance the harnessing of thermal energy efficiently. Phase change material (PCM) is a popular choice in thermal energy storage applications. On the other hand, the use of topology-optimised structures in heat sinks has been shown to enable a more effective transfer of heat from heat sources to the storage media. This project aims to conduct experimental investigations on a topology-optimised thermal energy storage device filled with novel phase change materials. The experiment investigations were conducted to compare the topology-optimised heat sink to a conventional fin-shaped heat sink. Three different types of PCMs were used and they were heated at three different power settings to obtain conclusive results. The topology optimised heat sink was found to perform better than the fin-shaped heat sink in all applications. In most experiments, the topology optimised heat sink was able to maintain base temperatures below a set point temperature for a longer time. In all experiments, the topology optimised heat sink was able to keep base temperatures lower than that of the finshaped heat sink. This suggests that the topology optimised heat sink is a more efficient cooling device as compared to the fin-shaped heat sink.